Design of an automated irrigation system for home gardens with IoT - Aldana Pulido, Deiber Andrés
The objective of the research is to develop an automated irrigation prototype for home gardens controlled with the Internet of Things (IoT) in the municipality of Santa María Huila. Their agricultural vocation allows the cultivation of a wide variety of products on a large scale and vegetables on a small scale in home gardens, however, they face low productivity since the result depends to a large extent on the weather (Prieto & Sendoa, 2017). The methodology developed is of the experimental development type, divided into the following phases: startup, software development and hardware development. As a result, the development of an automated irrigation system was obtained that allows real-time remote monitoring of ambient temperature and soil humidity through a graphical interface developed in the Arduino IoT Cloud, as well as the control of soil humidity. by means of a water pump created from the CAD design and the prototyping with 3D printing. The system is powered by photovoltaic solar energy, contributing to the protection of the environment, in addition to eliminating dependence on traditional and polluting energy sources.